Developing an Instructional Design-Based Dementia Education Program. (November 2022) - Ishimaru, Mina; Nagata, Akiko; Sato, Taichi; Sakai, Ayano; Suzuki, Satoko; Kubota, Kentaro
Community building is necessary to help create a dementia-inclusive society. In this study, a one-of-a kind dementia education program based on mutual learning using instructional design was developed alongside community members and stakeholders. The purpose was to implement and evaluate this program and gain insight into dementia education for the community. A total of 118 individuals participated in the program; however, data of 80 participants (Male = 26, Female = 54), who completed a questionnaire before and after the program, were analyzed. The results showed a significant pre–post difference in mean total scores on the Attitudes Toward Dementia Scale (32.1 points pre-program vs. 33.7 points post-program). Nine necessary learning topics were identified. The program could successfully teach participants to take the perspectives of various other people, view dementia as something relevant to themselves, and think about specific ways of responding to people with dementia considering their feelings. This study recommends creating education programs using scenario stories that depict the desire of people with dementia to be a part of the community, using visual depictions to create a shared impression and facilitate mutual learning.